Estimated public health impact of human rotavirus vaccine (HRV) and pneumococcal polysaccharide protein D-conjugate vaccine (PHiD-CV) on child morbidity and mortality in Gavi-supported countries. Issue 7 (30th December 2022) - Marijam, Alen; Schuerman, Lode; Izurieta, Patricia; Pereira, Priya; Van Oorschot, Désirée; Mehta, Shailesh; Ota, Martin OC; Standaert, Baudouin
ABSTRACT: Vaccine impact models against rotavirus disease (RD) and pneumococcal disease (PD) in low- and middle-income countries assume vaccine coverage based on other vaccines. We propose to assess the impact on severe disease cases and deaths avoided based on vaccine doses delivered by one manufacturer to Gavi-supported countries. From the number of human rotavirus vaccine (HRV) and pneumococcal polysaccharide protein D-conjugate vaccine (PHiD-CV) doses delivered, we estimated the averted burden of disease 1) in a specific year and 2) for all children vaccinated during the study period followed-up until 5 years (y) of age. Uncertainty of the estimated impact was assessed in a probabilistic sensitivity analysis using Monte-Carlo simulations to provide 95% confidence intervals. From 2009 to 2019, approximately 143 million children received HRV in 57 Gavi-supported countries, avoiding an estimated 18.7 million severe RD cases and 153, 000, deaths. From 2011 to 2019, approximately 146 million children received PHiD-CV in 36 countries, avoiding an estimated 5.0 million severe PD cases and 587, 000 deaths. The number of severe cases and deaths averted for all children vaccinated during the study period until 5 years of age were about 23.2 million and 190, 000, respectively, for HRV, and 6.6 million and 749, 000, respectively, for PHiD-CV. Models based on doses delivered help to assess the impact of vaccination, plan vaccination programs and understand public health benefits. In 2019, HRV and PHiD-CV doses delivered over a 5-y period may have, on average, averted nine severe disease cases every minute and one child death every 4 min. Plain Language Summary: What is the context? The WHO added the pneumococcal conjugate vaccine and the rotavirus vaccine in the recommended vaccination schedule of all countries in 2007 and 2009, respectively. Previous studies estimated the public health benefit of these vaccines by approximating the number of children who received them. What is new? We used an alternative approach to estimate the benefit based on actual number of doses of the vaccines, human rotavirus vaccine (HRV; Rotarix) and pneumococcal polysaccharide protein D-conjugate vaccine (PHiD-CV; Synflorix) delivered to each country considered. The study analyzed data from children under 5 years of age in 60 Gavi-supported countries by identifying the number of vaccine doses delivered, estimating the number of children fully covered, applying the country-specific disease epidemiology, estimating the number of severe disease cases and deaths avoided. From 2009 to 2019, approximately 143 million children were vaccinated with HRV avoiding an estimated 18.7 million severe rotavirus disease cases and 153, 000 deaths. From 2011 to 2019, about 146 million children were vaccinated with pneumococcal vaccine avoiding an estimated 5.0 million severe pneumococcal disease cases and 587, 000 deaths. What is the impact? The benefit of HRV and PHiD-CV in Gavi-supported countries is often estimated based on assumptions of vaccine coverage rates. A modeling approach based on doses delivered by the vaccine manufacturer can provide an additional view on the potential vaccine benefits and improve planning, contribution, and sustainability of the immunization programs at a country level. In 2019, HRV and PHiD-CV together averted nine cases of severe disease each minute and one child death every 4 minutes. Graphical Abstract: uf0001